Influence of Beta-cyclodextrin and Chitosan in the Formulation of a Colon-Specific Drug Delivery System - Rehman, K.; Amin, M. C. I. M.; Muda, S. (Drug Research, 2013)
The increase in diseases of the colon underscores the need to develop cost-effective site-directed therapies. We formulated a polysaccharide-based matrix system that could release ibuprofen under conditions simulating those in the colon by employing a wet granulation method. Tablets were prepared in a series of formulations containing a polysaccharide (beta-cyclodextrin and chitosan) matrix system along with ethylcellulose. We characterized physicochemical properties and performed an in vitro drug release assay in the absence and presence of digestive enzymes to assess the ability of the polysaccharides to function as a protective barrier against the upper gastrointestinal environment. Fourier transform infrared spectroscopy studies revealed no chemical interaction between ibuprofen and polysaccharides; however, spectrum analysis suggested the formation of an inclusion complex of beta-cyclodextrin with ibuprofen. The formulations contained 50% ethylcellulose and 50% beta-cyclodextrins (1:1) were proven to be the better formulation that slowly released the drug until 24 h (101.04±0.65% maximum drug release in which 83.08±0.89% drug was released in colonic medium) showed better drug release profiles than the formulations containing chitosan. We conclude that a beta-cyclodextrin drug carrier system may represent an effective approach for treatment of diseases of the colon.
Keywords: colon drug delivery; enzymatic digestion; inclusion complex; in vitro drug release; polysaccharide